Kegunaan Filsafat Ilmu Pada Pengembangan Scientific Method dalam Ilmu Hukum - Maulidin, Mohammad; Santoso, Fattah Setiawan; Priambodo, Eka; Purwanto, Ruli; Winarni, Harti (Universitas Cokroaminoto Yogyakarta, 2025)
Philosophy of science is useful for the development of legal science, with assumptions about ways of thinking, empirical results, and their limitations. Philosophy questions and analyzes the basis of observation, reasoning, including conclusions that underlie scientific methods in legal science. Through literature research, it can be seen that the epistemological and logical approaches, philosophy of science help understand the limitations and validity of scientific knowledge, and debate concepts such as objectivity, truth, and the reality of scientific methods to reveal current ways of developing legal science, such as abductive, deductive, and inductive. Philosophy of science and scientific methods complement each other and expand legal theory and practice.